Did that just happen?! : beyond "diversity"--creating sustainable and inclusive organizations - Pinder-Amaker, Stephanie, 1960-; Wadsworth, Lauren, 1987- (Beacon Press, 2021)
"Across the globe, organizations have begun to appreciate that diverse groups provide superior outcomes; however we do not know how to sustain diversity in the workplace. This book offers relatable vignettes and evidence-based skill building to close this gap"--